2
$\begingroup$

I have some homework that I am really struggling with (this class is above my level), and I would hope I could get some clarification.

I am given the geodesic equation $$\frac{\mathrm{d}^{2}x^{\mu}}{\mathrm{d}\lambda^{2}} + \Gamma ^{\mu}{}_{\alpha\beta}\frac{\mathrm{d}x^{\alpha}}{\mathrm{d}\lambda}\frac{\mathrm{d}x^{\beta}}{\mathrm{d}\lambda} = 0,$$ the FRW metric in the form $$\mathrm{d}s^{2} = \mathrm{d}t^{2} - a^{2}(t) \left[\frac{\mathrm{d}r^{2}}{1-\kappa r^{2}} + r^{2} \left( \mathrm{d}\theta^{2} + \sin^{2}\theta \mathrm{d}\phi^{2}) \right)\right],$$ and we are looking at a photon that has a 4-momentum of the form $$ \rho^{\mu} = \frac{\mathrm{d} x^{\mu}}{\mathrm{d}\lambda},$$ with the photon's 3-momentum being $ \rho^{i} = 0 $, and $ E = \rho^{0} $.

We are assuming that the photon travels in the radial direction, and we are working in null geodesics.

The point of the exercise is proving that $ E^{2} - \frac{a^{2}}{1-\kappa r^{2}}(\rho ^{1})^{2} = 0.$

Taking $E = \rho^{0} = \frac{\mathrm{d}x^{0}}{\mathrm{d}\lambda}$, then the first term of the geodesic equation is equal to $E^{2}$. With a similar approach, the terms to right of the Christoffel symbol can be $(\rho^{1})^{2}$ if $ \alpha = \beta = 1 $ (and because in the 4 momentum, as it is traveling radially, the other terms are 0), we are left with $$E^{2} + \Gamma^{0}{}_{1,1} (\rho^{1})^2) = 0$$

This is fairly close to the answer I am looking for, but the Christoffel symbol for $\Gamma^{0}{}_{1,1}$ is $\frac{a\dot{a}}{1-\kappa r^{2}}$.

I know that working backwards is not the best idea, but I am quite lost. I think that I am either quite lost and there is something very obvious that I am not seeing, or that my approach is fundamentally wrong. I hope you can help me, and thank you.

$\endgroup$

1 Answer 1

1
$\begingroup$

Radial geodesics have $\frac{\mathrm{d}\theta}{\mathrm{d}\lambda} = \frac{\mathrm{d}\phi}{\mathrm{d}\lambda} = 0$. Furthermore, for null geodesics $\mathrm{d}s^2=0$ so $$ 0 = \left( \frac{\mathrm{d}t}{\mathrm{d}\lambda} \right)^2 - \frac{a(t)^2}{1-\kappa r^2} \left( \frac{\mathrm{d}r}{\mathrm{d}\lambda}\right)^2 = E^2 - \frac{a^2}{1-\kappa r^2} (\rho^1)^2. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.